Two-dimensional models in quantum field theory: Reduction to the free-particle case - Dutra, Alvaro de Souza [UNESP]; Hott, Marcelo [UNESP] (American Physical Soc, 1991)
We demonstrate that the generating functionals for two-dimensional models with two real scalar fields, one interacting with an external electromagnetic field and the other with coupling terms but without external fields, can be reduced to the case of the free-particle propagator when quasistatic solutions for this theory are used. © 1991 The American Physical Society.